2023
DOI: 10.1002/anie.202305804
|View full text |Cite
|
Sign up to set email alerts
|

Going Beyond Silver in Ethylene Epoxidation with First‐Principles Catalyst Screening

Abstract: Ethylene epoxidation is industrially and commercially one of the most important selective oxidations. Silver catalysts have been state‐of‐the‐art for decades, their efficiency steadily improving with empirical discoveries of dopants and co‐catalysts. Herein, we perform a computational screening of the metals in the periodic table, identify prospective superior catalysts and experimentally demonstrate that Ag/CuPb, Ag/CuCd and Ag/CuTl outperform the pure‐Ag catalysts, while they still confer an easily scalable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 68 publications
0
1
0
Order By: Relevance
“…This work reinforces that even though the "ground truth" of ethylene epoxidation is very complicated, simpler, single site models can still recreate the majority of the trends in catalytic activity. Given the broad predictability of the HH model when lateral interactions are included, 27 and that the epoxidation of ethylene can occur on multiple different sites simultaneously, 9 it is most likely that all of these models contain some core truth within them, and that further transient experiments of ethylene epoxidation are required to identify the true reaction mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…This work reinforces that even though the "ground truth" of ethylene epoxidation is very complicated, simpler, single site models can still recreate the majority of the trends in catalytic activity. Given the broad predictability of the HH model when lateral interactions are included, 27 and that the epoxidation of ethylene can occur on multiple different sites simultaneously, 9 it is most likely that all of these models contain some core truth within them, and that further transient experiments of ethylene epoxidation are required to identify the true reaction mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…4 To approximate lateral interactions, the pairwise interaction between the adsorbates was assumed be a maximum at a coverage of 1, with a linear dependence on coverage, which has been shown to be generally correct for transition metal surfaces, 29 but it should be mentioned that reality is often more complex, with nonlinear scaling reported for EO formation recent studies. 30 Step 1 was modified such that:where E a,rev ( θ O* ) is the calculated activation barrier, E a,rev (0) is the activation barrier at zero coverage, is the pairwise interaction between O* and the adsorbate, and θ O* is the coverage of O*. Step 5 was modified using the following expression: E a,fwd ( θ O* ) = E a,fwd (0) + E OME pairwise θ O* With step 6 fwd , 7 rev , and 8 rev also modified using eqn (16).…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrates that single-site models, when accounting for lateral interactions, can replicate more complex kinetic features observed during the experiments, which can explain this models broad predictability for EO production across a wide range of materials. 30 However, further refinement of the combustion pathway is required in order to precisely recreate the selectivity trends as a function of surface oxygen coverage. As to why the lateral interactions cause this initial increase in both EO and CO 2 production, we find that it is a combination of the increased stabilisation of and decreased stabilisation of OME* as a function of oxygen surface coverage.…”
Section: Discussionmentioning
confidence: 99%
“…As an important industrial process, the selective oxidation of ethylene to ethylene oxide (EO) was extensively studied, [30] the high EO selectivity was generally achieved at the expense of ethylene conversion, [31][32][33][34] mainly because active oxygen species involved in the catalytic process were not adequately understood. [35][36][37][38][39] In addition, two highly thermodynamically favored side reactions, i.e., the total oxidation of ethylene (ΔH of À 1327 kJ/mol), and the oxidation of EO (ΔH of À 1223 kJ/mol), accompany the desired selective oxidation of ethylene to EO. Recently, we have proposed a molecular-like catalysis strategy for ethylene epoxidation, and found that surface-adsorbed molecular oxygen directly participated in the reaction.…”
Section: Introductionmentioning
confidence: 99%